Building Brand Awareness through Social Media: Analysis of Effective Content Strategies in E-Commerce Businesses in Indonesia - As-Syahri, Hidayatullah; Abidin, Fairuz Zabadi Zainal (AL-QARDH, 2024)
This study aims to analyze effective content strategies for building brand awareness through social media in e-commerce businesses in Indonesia. With the rapid growth of the e-commerce industry and the high level of social media usage in Indonesia, companies need to implement appropriate digital marketing strategies to enhance their brand visibility and recognition.This research adopts a literature study approach, analyzing social media content from five leading e-commerce companies in Indonesia: Tokopedia, Shopee, Bukalapak, Blibli, and Lazada. The types of content examined include videos, images, and text published on various social media platforms, such as Instagram, YouTube, TikTok, and Facebook. The data sources consist of industry reports, academic articles, and relevant secondary data from platforms such as iPrice, Tempo, and Bisnis.com.This study employs descriptive and comparative analysis methods to evaluate the content strategies implemented by each company. It focuses on the effectiveness of different types of content in increasing audience engagement and their contribution to improving brand awareness.The findings of this study indicate that social media is a highly effective tool for building brand awareness for e-commerce companies in Indonesia. Strategies such as the use of influencers, creative content, interactive videos, and live streaming have been proven to enhance engagement and brand visibility. These findings highlight that a combination of creativity, authenticity, and interactivity in social media content strategies plays a significant role in strengthening brand awareness in the e-commerce sector.Based on these findings, it can be concluded that a combination of content strategies that include promotion, education, and direct interaction with the audience is highly effective for building brand awareness on social media. Companies are also recommended to utilize influencer marketing and live streaming features, as these approaches have been proven to strengthen emotional connections between brands and consumers.